Superando o estigma da seca a partir de estratégias de convivência com o semiárido: o modelo da comunidade de Sussuí, Quixadá, Ceará. - Torquato, Renata Ribeiro (2011)
This Work has as purpose investigate the numerous strategies known as practices of acquaintanceship with the semiarid, having has a base the environmental history, the permaculture, the principles of agroecology and practices of environmental education. The study was carried out in the community of Sussuí, Quixadá, Ceará Central Hinterland, place where develops the Project of Community Integration with aid of Instituto Nordeste Cidadania – INEC. The dry’s problem is reassessed from a new perspective that seeks to live with the peculiarities and potentialities of the region. The drought’s problem doesn’t begin with lack of water and doesn’t end with arrival of rain station. There simply comes from the loss of agricultural production shortage, absence or rain’s irregularities. Fundamentally, the drought has direct connotations with periodic crises that affect the agricultural economy by unsuitability of crops produced with the conditions of potential and limitations of natural resources. In addition, others factors can aggravate like this, weathers change and the inappropriate manipulation of the natural resources. The Permaculture, the agroecology and the education work within the perspective of acquaintanceship with the semiarid, through of practices and alternatives handles that respect the environment ant optimizes the use of nature resource as well as guiding people to develop a new way of dealing with the peculiarities of a region subject to irregular rainfall.